Morphofonemical Verba In Kerinci Language - Eva Fitrianti (Jurnal Ilmiah Langue and Parole, 2017)
Research on the morphophonemic process of Kerinci language verb is done with the background of many linguistic problems that have not received attention in Kerinci language and very little documentation has been done to the language of Kerinci. This research is done with awareness of the effort to conserve one of the elements of culture, namely language. This research is a qualitative research with descriptive method, which aims to describe Kerinci language empirically based on the situation or facts that exist in the field and presented with what it is. The informant is a native speaker of Kerinci. Data collection techniques used are recording techniques, elasticity techniques, and techniques refer. Data analysis technique used in this research is transcribing data into writing language, translating data into Indonesian, and analyzing data. To facilitate the analysis, the data already written and translated into Indonesian language is then classified by word category. The result of this research is that there are four rules of morphophonemic process of verb forming affix, ie {maN-}, N-, {bar-}, and {ta-}. The four rules of verb-forming merbophonemic in Kerinci, can be classified again into two processes: phoneme change and phoneme removal processes.